Wisata Gastronomi Berbasis Budaya Lokal Sebagai Upaya Pengembangan Makanan Tradisional Di Kota Pekalongan - Disma, Fatimatuz Zahra; Widiyanto, Nur; Kusumawati, Pipin (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2025)
Gastronomy tourism, particularly that based on traditional food in Pekalongan City, has not developed optimally. This is due to the weak integration of local cultural identity into culinary tourism development, as well as the lack of synergy among stakeholders such as the government, business actors, academics, communities, and the media. As a result, both locals and tourists tend to choose food from outside the region or modern cuisine that is more popular. This study aims to identify the inhibiting factors in the development of culture-based gastronomy tourism and to formulate effective strategies for preserving and developing traditional food as a tourism attraction in Pekalongan City. The method used is a descriptive qualitative approach with in-depth interview techniques involving various relevant informants. The results of the study show that the potential of Pekalongan’s traditional culinary products—such as megono, tauto, gemblong, kopi tahlil, and other local snacks—has not been fully optimized. The main problems include the lack of integrated promotion and branding, low innovation among business actors, and challenges posed by modern culinary trends. Traditional food has not been able to attract the interest of the younger generation and tourists due to low community participation in gastronomy tourism development. In addition, the packaging and presentation remain conventional. The conclusion of this study emphasizes that effective gastronomy tourism development strategies must integrate local cultural values into a holistic gastronomic approach. Active community involvement, education through culinary storytelling, product and packaging innovation, as well as the utilization of digital technology, are key to adaptive preservation. Cross-sector collaboration through the Nona Helix approach is necessary to strengthen cultural identity and enhance the competitiveness of traditional food as a sustainable tourism asset in Pekalongan City